2008
DOI: 10.1016/j.wear.2008.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of boundary lubricating additives on DLC coatings

Abstract: The friction properties of a range of boundary lubricating additives in DLC-DLC rolling-sliding contact have been investigated. Two types of commercial DLC have been studied, one hydrogenated diamond-like and the other Cr-doped, nonhydrogenated and graphitic.The graphitic-type DLC coating initially gave very low boundary friction with additive-free base oil but after a few minutes of rubbing in thin film conditions friction rose to a higher value, similar to that produced immediately by the diamondlike carbon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(56 citation statements)
references
References 20 publications
2
49
0
1
Order By: Relevance
“…DLC coatings are becoming quite widely used for machine elements in lubricated systems, especially in the automotive industry (He,et al (8); Gangopadhyay,et al (9)), as well as under high stress and/or under boundary or mixed lubrication regimes (Kalin,et al (10); Manier,et al (11)). Topolovec, et al (12) studied the friction properties of a range of boundary lubricating additives in DLC rolling-sliding contacts and analyzed how these coatings interacted with the various additives present in the formulated lubricants and the impact of additive-DLC interactions on friction and wear. Kalin,et al (10) studied the DLC-lubricant interaction and analyzed only DLC-DLC contacts in order to avoid the inevitable effects from interactions with other countermaterials such as steel.…”
Section: Introductionmentioning
confidence: 99%
“…DLC coatings are becoming quite widely used for machine elements in lubricated systems, especially in the automotive industry (He,et al (8); Gangopadhyay,et al (9)), as well as under high stress and/or under boundary or mixed lubrication regimes (Kalin,et al (10); Manier,et al (11)). Topolovec, et al (12) studied the friction properties of a range of boundary lubricating additives in DLC rolling-sliding contacts and analyzed how these coatings interacted with the various additives present in the formulated lubricants and the impact of additive-DLC interactions on friction and wear. Kalin,et al (10) studied the DLC-lubricant interaction and analyzed only DLC-DLC contacts in order to avoid the inevitable effects from interactions with other countermaterials such as steel.…”
Section: Introductionmentioning
confidence: 99%
“…It is natural to consider that the wear process increases the contact area and generates a conformal contact susceptible to strongly modify the contact parameters (contact pressure), which can be at the origin of the friction reduction process. Moreover, Topolovec-Miklozic reported that the formation of a GMO-derived tribofilm is needed by the contribution of a bulk fluid film [40]. This indicates that the increment of the contact area supported the formation of a GMO-derived tribofilm.…”
Section: Discussionmentioning
confidence: 94%
“…Owing to the considerable amount of research, it is well-known that the tribological behavior of a DLC film depends on various factors such as atmospheric conditions [1][2][3][4][5][6], counter-materials [7][8][9], and the type of lubricant [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In particular, the tribological behavior of a DLC film is governed by graphitization of the DLC film under dry sliding conditions [24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [25] used a nano-indenter to investigate tribo-film hardness and elasticity of an ashless extreme-pressure additive generated through tribological tests. Topolovec-Miklozic et al [26,27] used a mini-traction machine (MTM) to investigate ZDDP tribo-film formation on DLC. After the surface was lightly cleaned with propanol, surface height and lateral force images measured using an AFM were used to gain an understanding of the tribometric results.…”
Section: Introductionmentioning
confidence: 99%